Evaluation on the Rheological Properties of Water-Based Drilling Mud: A Case Study of Ire-Ekiti Clay - Joseph O. AJAYI; Adekunle T. ADENIYI; Mufliah G. OMOFOYEWA; Abel A. ADEYI; Abdulwahab GIWA (FUDMA Journal of Engineering and Technology, 2026)
Rheological properties are tested throughout a drilling operation as it is critical in the control and maintenance of rheological properties. This paper investigates the evaluation on the Marsh funnel viscosity, apparent viscosity, and fluid loss of water-based drilling mud. The native clay originated in Ire-Ekiti, Ekiti State, Nigeria. In order to create water-based mud, the characteristics of the clay were determined and compared with those of bentonite, the preferred clay for drilling operations. The results show that the generated drilling fluid's pH levels and rheological characteristics differ significantly from bentonite. This is due to the fact that it attracts clay and water, and the low concentration of sodium cations (Na++) prevents it from swelling. When the local mud was beneficiated using soda ash (Na2CO3) at a concentration of 5.0 g clay at 63 microns screen size to 350 ml of the mud, the pH rose by 15.2% from 8.11 to 11.02 and by 8% from 10.00 to 11.73. When PAC-HV was added to the combination, water loss significantly decreased by 32.8% and 66.8%, while marsh funnel viscosity increased by 4.4% and 7.6%, apparent viscosity fell by 26.6% at 63 microns sieve size, and severely rose by 55.8% at 150 microns filter size. After adding 10 g of barite (BaSO4) to 350 ml of the mixture, the clay density rose by 1.2% at both sieve sizes, from 8.50 lb/gal to 8.70 lb/gal. Therefore, the Ire clay has good rheological properties at substantial concentrations when beneficiated with soda ash (Na2CO3), which would compare favorably with those of bentonite; however, PAC-HV must be increased above 1.0 g at 150 microns filter size. Ire clay can therefore be used to make a drilling fluid.
Keywords: Ire-Ekiti clay, beneficiation, bentonite, rheological properties, water-based mud.